Demand side considerations and the trade and wages debate - Abrego, Lisandro; Whalley, John 1947- (National Bureau of Economic Research <Cambridge, Mass.>: NBER working paper series, 2000)
Recent trade and wages literature focuses on whether trade or technology has been the major source of increases in wage inequality in OECD countries since the 1980s. In this literature, no attention has been paid to demand side considerations. Using a simple heterogeneous goods trade model of the Armington type, and UK data, we show how trade shocks affecting the price of unskilled-intensive goods can be absorbed on the demand side, with little or no impact on relative wage rates. No wage impact occurs if the elasticity of substitution in preferences between imports and import substitutes is one. As this elasticity increases, trade plays an ever larger role in explaining wage inequality changes, and as the elasticity goes below one the sign of the effect changes. We suggest that since many import demand elasticity estimates are in the neighbourhood of one, there is a prima facie case that demand side considerations further lower the significance of trade as an explanation of recent trends in OECD wage inequality -beyond that reported in recent literature.